Acceptance of assisted partner notification among HIV-positive adults with severe mental illness at a national referral hospital in Uganda: a cross-sectional study - Nante, Rachel Wangi; Muyinda, Herbert; Kiweewa, John M; Ndagire, Regina; Ssendikwanawa, Emmanuel; Ojiambo, Kevin Ouma; Nangendo, Joanita; Nakku, Juliet; Semitala, Fred C (BioMed Central Ltd, 2024)
Abstract HIV mostly affects people with severe mental illnesses (SMIs) than the general population. In 2015, the World Health Organization (WHO) introduced assisted partner notification (APN) as a strategy to increase HIV testing. Although research has demonstrated the effectiveness of APN in the general population, its use among people living with HIV (PLHIV) who have SMI is not well understood. This study sought to determine the acceptance of the APN strategy among PLHIV who had a diagnosis of SMI. This study used a cross-sectional study design that was retrospective to determine acceptance of APN among PLHIV with a documented diagnosis of SMI. We enrolled participants with a diagnosis of both HIV and SMI from August 2018 to January 2022, attending the HIV clinic at Butabika Hospital. We used pretested questionnaires to extract participants' demographic and clinical data from their existing clinical charts, antiretroviral therapy (ART) registers and APN registers. We defined acceptance of APN as the number of PLHIV with SMI diagnoses who agreed to provide information about their sexual partners. We used modified Poisson regression analysis to assess the factors associated with the acceptance of APN. A total of 125 participants were enrolled, of whom 83 (66.4%) were female. The median age was 30 (interquartile range (IQR) (25-34)), and 41 (33%) of them accepted APN (95% CI: 25.05-41.61). Receipt of at least three counselling sessions before enrollment in APN (aPR = 1.8, 95% CI: 1.72-1.98) was the most significant factor associated with increased acceptance of APN. Poor adherence to ART (aPR = 0.62, 95% CI: 0.54-0.80), being escorted to hospital by a distant relative (aPR = 0.55, 95% CI: 0.39-0.80), being married/cohabiting (aPR = 0.65, 95% CI: 0.60-0.81), and being a Seventh Day Adventist (SDA) (aPR = 0.53, 95% CI: 0.45-0.71) or Pentecostal (aPR = 0.44, 95% CI: 0.22-0.98) by faith were associated with reduced acceptance of APN. The acceptance of APN is low among PLHIV with a diagnosis of SMI. More structured counselling would facilitate earlier identification of undiagnosed HIV-positive partners. We recommend a follow-up study to compare acceptance of APN among PLHIV with SMI and those without SMI.
Keywords: Assisted partner notification, HIV, Severe mental illness, Acceptance